The effects of combined strength and endurance training - Hennessy, L. C.; Watson, A. W. S.
The levels of strength and endurance needed for sport vary depending on the particular sport chosen. Some are predominantly strength based, while others are more endurance based, with most others requiring intermediate combination of the two. Physiological adaptations of the body are specific to the type of training undertaken.